A review of Hippeutister Reichensperger with new species from California and Costa Rica (Coleoptera: Histeridae: Hetaeriinae) - Caterino, Michael S.; Tishechkin, Alexey K. (Zootaxa, 2008)
The myrmecophilous genus Hippeutister Reichensperger, 1935, contains six species, known from scattered localities in North, Central and South America. Two of these, H. californicus n. sp. and H. solisi n. sp. are newly described herein. The other four are H. manicatus (Lewis) (=H. solenopsidis Reichensperger, syn. nov.), H. plaumanni Reichensperger, H. castaneus (Lewis), and H. amabilis (Wenzel). The genus is likely monophyletic, and is easily recognized by the presence of a very broad prosternal keel, which is deeply triangularly incised at the base. Species of Hippeutister are unusual among hetaeriine Histeridae in their occurrence in the nests of fire ants (Solenopsis spp.)